Children’s Rights: Comparison of The Consciousness Levels of Gifted and Non-Gifted Children - Koca, Selda; Senol, Fatma Betul; Erbasan, Ömer; Aktepe, Gülenay Esranur (Southeast Asia Early Childhood Journal, 2023)
The study was conducted to examine the consciousness levels of gifted children about children’s rights and to compare them with their non-gifted peers. The general survey model was used in this study, in which the consciousness levels of gifted and non-gifted children on children’s rights were compared. The study group of the research consists of 63 gifted and 65 non-gifted primary school students studying in a science and art center in Afyonkarahisar. In the research, the "Children’s Rights Consciousness Level Determination Scale" developed by Akgül and Çağlayan (2019) was used to determine the consciousness levels of students about children’s rights. In the analysis of the collected data, the difference between the groups was examined with the Mann Whitney U test using the data analysis program. As a result of the research, the consciousness level of gifted students about children’s rights was found to be significantly higher than their non-gifted peers. In addition, this difference emerged in the "right to information and opinion" dimension of the scale. The unique developmental characteristics of gifted children may have an impact on their knowledge, consciousness and behavior towards children’s rights. However, there is a need for comparative and longitudinal large-scale studies based on epidemiological data on the sensitivity of gifted children to children’s rights. In addition, educational and behavioral interventions should be made in order to increase the consciousness of gifted children about children’s rights, regardless of their educational environment.